PEMANFAATAN BAHAN ALAM DALAM KONSERVASI DAN ANALISIS PRASASTI TIMAH - Prakoso, Nurcahyo Iman; Alifia Tia , Aulia; Ria Diar Stya, Primastiti (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2025)
Artifact preservation efforts require conservation approaches that are environmentally friendly and compatible with the original materials of the object. This study examines the use of natural materials in artifact conservation, focusing on three main materials: rabbit skin glue as an adhesive, beeswax as a protective layer, and compositional analysis on tin inscriptions. FTIR testing showed the presence of protein content in rabbit skin that can produce gelatin to be used as an adhesive. Rabbit skin glue adhesion testing was conducted on ceramic and wood media with various glue concentrations (5%, 10%, 15%, 20%, and 37.5%) under humid conditions (90% humidity and 26°C temperature) for three consecutive days. The test results showed that on the third day, only the 37,5% concentration was able to survive. In the colorimetric test, the average value of ∆E was still below 4, thus, rabbit skin glue is still safe to be used in conservation. In the case of beeswax, the mixture of beeswax with olive oil proved to be superior to the mixture of beeswax with turpentine, as it produced a more even, glossy coating, and provided better protection against moisture and prevented mold growth more effectively. XRF analysis of the tin inscriptions revealed that the main composition of the inscriptions was tin (Sn) with the highest content of 93,145% in inscription D, while lead (Pb) was found with the highest content of 21,755% in inscription A. Overall, this study shows that natural materials such as rabbit skin glue and beeswax have good potential in artifact conservation applications, providing a safer and more effective alternative compared to synthetic materials, especially in maintaining the authenticity and durability of artifacts against damaging environmental influences.